Love is love : a comic book anthology to benefit the survivors of the Orlando Pulse shooting (IDW Publishing, 2016)
"The comic book industry comes together to support the survivors and honor those killed at the Pulse nightclub in Orlando, Florida, on June 12, 2016. Writers and artists from across the globe have created exclusive new material expressing their sorrow, compassion, frustration, and hope, all inspired by the tragic events. In doing so, they celebrate the victims, survivors, and their families while also spreading a message of peace and inclusion" -- page 4 of cover.